Neurologic outcomes of surgery and anesthesia - Mashour, George A. (George Alexander), 1969-; Avidan, Michael (Oxford University Press, 2013)
Most of the developments in perioperative medicine the 20th century were focused on the establishment of standard monitors, biomarkers, and outcomes measures for the cardiovascular and respiratory systems, with marked improvements in perioperative safety. The fields of anesthesiology and perioperative medicine have now shifted to the consideration of the nervous system. Complications such as delirium, cognitive decline, anesthetic neurotoxicity, stroke and other devastating nervous system events are only now developing significant scientific and clinical attention.